Motor unit discharge rate in dynamic movements of the aging soleus - Kallio, Jouni; Søgaard, Karen; Avela, Janne; Komi, Paavo V.; Selänne, Harri; Linnamo, Vesa (Frontiers in Human Neuroscience, 2014)
Aging is related to changes at the muscular level, leading to a decline in motor performance increasing the risk of falling and injury. It seems that the age-related changes in motor unit activation are muscle- and intensity dependent. The purpose of this study was to examine possible differences in soleus motor unit discharge rate (MUDR) in both isometric and dynamic contractions between young and elderly adults. 11 young (YOUNG) and 8 elderly (OLD) males participated in the study. The subjects performed isometric and dynamic plantar flexions while seated in an ankle dynamometer. The force levels studied were 10, 20, 40, 60, 80 and 100% of the isometric (ISO) MVC in ISO and 10, 20 and 40% in concentric (CON) and eccentric (ECC) contractions. Soleus intramuscular EMG was recorded with bipolar fine-wire electrodes and decomposed to individual trains of motor unit discharges. In ISO the MUDR was higher in YOUNG in 20, 40, 60 and 80% MVC, while in the dynamic contractions no age-difference was seen. For both age-groups MUDR was higher in CON compared to ISO or ECC. The relative level of sEMG activity in SOL and GM for a given force level was in all conditions higher for OLD compared to YOUNG. The decreased MUDR in OLD may be an adaptation to an increased twitch duration in order to optimize force generation. The lack of an age-difference in dynamic contractions could be due to differences in recruitment-strategies, coactivation or a lack of recording from high force levels.